Addressing Special Educational Needs and Disability in the Curriculum: Design and Technology - Davies, Louise T. (London : Taylor and Francis, 2017)
"The SEND Code of Practice (2015) reinforced the requirement that all teachers must meet the needs of all learners. This topical book provides practical, tried-and-tested strategies and resources that will support teachers in making design and technology lessons accessible and interesting for all pupils, including those with special educational needs. The author draws on a wealth of experience to share her understanding of special educational needs and disabilities and show how the design and technology teacher can reduce or remove any barriers to learning. Offering strategies that are specific to the context of design and technology teaching, this book will enable teachers to:better identify a student's particular learning requirements; set inclusive design and making assignments which allow all students to participate and succeed;build students' confidence in using a range of materials and tools;assist with design tasks where pupils take ownership of their work and learning;adapt the classroom environment to meet the needs of pupils; create a mutually supportive classroom which maximises learning opportunities.An invaluable tool for continuing professional development, this text will be essential for design and technology teachers (and their teaching assistants) seeking to include and motivate all pupils in their lessons, regardless of their individual needs. This book will also be of interest to secondary SENCOs, senior management teams and ITT providers. In addition to free online resources, a range of appendices provide design and technology teachers with a variety of pro forma and activity sheets to support effective teaching. This is an essential tool for design and technology teachers and teaching assistants, and will help to deliver successful, inclusive lessons for all pupils. "--Provided by publisher.
chapter 1 Meeting special educational needs and disabilities: Your responsibility -- chapter 2 Starting points: Different types of SEND in D&T -- chapter 3 An inclusive environment for D&T lessons -- chapter 4 Teaching and learning -- chapter 5 Special designers and makers -- chapter 6 Monitoring and assessment -- chapter 7 Managing support -- chapter 8 Real pupils in real classrooms.
Keywords: Special education -- Curricula; Technical education; Technological literacy; Technology -- Study and teaching (Secondary).; Industrial design -- Study and teaching (Secondary).; Creativity; Inclusion and Special Educational Needs; SENCOs; Technology in Education; EDUCATION / Special Education / General; EDUCATION / Teaching Methods & Materials / Science & Technology